Концептуальні положення щодо ведення інформаційної боротьби в інформаційній сфері при веденні сучасних війн - Кучеренко, Юрій Федорович; Александров, Олександр Валерійович; Носик, Андрій Михайлович; Возний, Олександр Олександрович (Харківський національний університет Повітряних Сил ім. І. Кожедуба, 2023)
У статті розкриті особливості ведення сучасних війн, які стають більш інформаційними, бо в них відбувається проведення певних широкомасштабних інформаційних дій, направлених проти суспільства, соціальних та державних інформаційно-технічних систем і, в першу чергу, систем управління військового призначення, з метою отримання інформаційної переваги над противником. Показано, що в умовах, коли здійснюється повномасштабна збройна агресія Російської Федерації (РФ) проти нашої країни, відбувається жорстка боротьба в інформаційній сфері, в якій проводяться інформаційні (психологічні) операції з боку РФ, а також різні гібридні дії, що спрямовані на підрив національної безпеки України, її національних інтересів та її світового іміджу. Визначені основні складові і напрямки ведення інформаційної боротьби та представлений процес здійснення впливу елементів і засобів ведення інформаційної боротьби на складові інформаційної сфери країни, що є загальноутворюючою основою для функціонування всіх складових національної безпеки держави. Наведені концептуальні положення стосовно ведення інформаційної боротьби в інформаційній сфері при веденні сучасних війн. Даний матеріал може бути використаним як керівним складом, так і науковцями збройних сил при аналізі впливу зовнішніх та внутрішніх факторів на інформаційну сферу країни з метою здійснення впливу на інформаційну сферу супротивника та надійного захисту своїх складових інформаційної сфери, як-то: інформаційних ресурсів, інформаційної інфраструктури та суб’єктів інформаційної діяльності.

The article reveals the peculiarities of modern wars, which are becoming more informational, since they involve certain large-scale information actions directed against society, social and state information and technical systems, and, first of all, military command and control systems, with the aim of gaining an information advantage over the enemy by reducing the time of cycles of command and control of troops and means on the battlefield. It is shown that in modern conditions, when the Russian Federation's large-scale armed aggression against our country is being carried out, there is a fierce struggle in the information sphere of our country, in which information (psychological) operations are being conducted by the Russian Federation, as well as various hybrid actions aimed at undermining Ukraine's national security, its national interests and its world image, destabilizing the socio-political and socio-economic situation in the country, the protection of the information sphere is of great importance. The article defines the main components and directions of information warfare, reveals the main components of the information sphere and presents the process of influence of elements and means of information warfare on the components of the country's information sphere, which is the general forming basis for the functioning of all components of the national security of the State, especially in the context of the Russian Federation's full-scale armed aggression against Ukraine. The article provides conceptual provisions on conducting information warfare in the information sphere in modern wars. This material should be used by both the leadership and scientists of the armed forces in analysing the impact of external and internal factors of influence, as well as information tools and elements of information warfare in the information sphere in order to ensure the implementation of measures to reliably protect information resources, information infrastructure and subjects of information activity from their negative actions.
Conceptual provisions for conducting information warfare in the information sphere in modern wars
Keywords: війна; вплив; засоби; інформація; інформаційна боротьба; інформаційна операція; інформаційна сфера; концептуальні положення; процес; психологічна операція; war; influence; means; information; information warfare; information operation; information sphere; conceptual provisions; process; psychological operation